Starlight Vattano. Didattica del segno percorsi pedagogici, Franco Angeli, Milano, 2020 (diségno, 2020)
Francesca Fatta in the Preface of the book Didattica del segno, percorsi pedagogici by Starlight Vattano, published by Franco Angeli in the open-access edition, writes that children drawing “can visibly and durably express the imagination, emotion, sensation and thought of the person who performs it, almost as if to draw a tangible sign of himself” (read more).